(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2025)
Breast cancer is the most commonly diagnosed cancer and the leading cause of death among female patients, which seriously threatens the health of women in the whole world. The treatments of breast cancer require the cooperation of a multidisciplinary setting and taking tumour load and molecular makers into account. The incidence of breast cancer is constantly increasing in all regions of the world. For this reason, despite the progress in its detection and treatment, which translates into improved mortality rates, it seems necessary to look for new therapeutic methods, and predictive and prognostic factors. Triple negative breast cancer is responsible for more than 15–20% of all breast cancers. Future therapeutic concepts for breast cancer aim to individualize therapy and de-escalate and escalate treatment based on cancer biology and early response to therapy. The article presents a review of the literature on breast carcinoma—a disease affecting women in the world.